Influence du mode de plantation sur le taux de mortalité, la vigueur et le rendement de deux variétés d'amandier (Achaak et Ksontini) plantées en région aride - El Gharbi A.; Triki H.; Dumont H. (Séminaire du GREMPA sur les portes-greffes de l'amandier, 1989)
Two different planting systems were studied at the experimental orchard of Etiaous, Sfax, in order to evaluate their performance: seedlings grafted at the nursery and transplanted or grafted at their definitive site. The test lasted 15 years (1973-1987). The analysis of the results have shown the better behaviour of the plants grafted on site than those grafted at the nursery as regards to tree death, root system spreading, vigour and production.
Séminaire du GREMPA sur les portes-greffes de l'amandier, 1988/11/29-30, Saragoza (Spain)